Single-valuedness problem on charge density wave rings. (5th November 2015) - Hosokawa, T.; Matsuura, T.; Tsubota, M.; Tanda, S.
Abstract: We investigate the bimodal fluctuation of charge density wave (CDW) current through ring-shaped crystals (typical diameter is a few ten ) of orthorhombic tantalum trisulfide . We find that the CDW current changes between two types of the bimodal fluctuation, and exhibits hysteretic behavior as a function of the dc voltage. The hysteresis of the fluctuation modes suggests that the CDW rings involve several metastable sliding states, which might be a manifestation of single-valuedness of the CDW phase field with a strong periodic boundary condition of the ring geometry.